Effect of Amplitude and Confining Pressure on Granite Failure under Ultrahigh Frequency (UHF) Impact Based on Radiation Temperature. (20th September 2022) - Zhang, Cheng; Zhang, Shulei; Zhao, Dajun
Abstract : Ultrahigh frequency impact technology has great potential to break hard rocks with lower energy consumption. Based on the infrared nondestructive testing technology, the effects of load (i.e., amplitude) and boundary (i.e., confining pressure) conditions on granite damage under ultrahigh frequency impact have been investigated to promote the application of this technology in rock engineering. Experimental results demonstrate that the evolution law of the maximum radiation temperature on granite surface reflects the granite damage state. Under ultrahigh impact, granite specimens are damaged effectively with the impact amplitude exceeding 32 μ m, and the failure mode of the specimen is changed by the confining pressure. Depending on Griffith's theory, the extension angle of the fatigue crack changes from 60 to 30 degrees with increasing confining pressure. And the transverse fracture occurs in the upper part of the specimen under ultrahigh frequency impact subjected to confining pressure. This research determines the amplitude threshold of the ultrahigh frequency impact load and verifies the effectiveness of ultrahigh frequency impact technology for granite failure subjected to confining pressure.